DATABASE NORMALIZATION: OPTIMIZING DATA MANAGEMENT (Journal of Universal Science Research, 2024)
This article introduces the process of structuring a database to reduce redundancy and improve data integrity. The use of normal forms such as 1NF, 2NF, 3NF, 4NF, 5NF and BCNF and their differences are covered.